1997
DOI: 10.1172/jci119136
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of proinflammatory cytokines by epithelial cells in response to Chlamydia infection suggests a central role for epithelial cells in chlamydial pathogenesis.

Abstract: Chlamydia species infect epithelial cells at mucosal surfaces, and are major causes of sexually transmitted diseases. Infection is characterized by inflammation which is exacerbated upon reinfection, ultimately leading to tissue damage and scarring. Although central for the development of disease manifestations, little is known about the mechanisms that initiate and sustain the inflammatory response to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
386
4
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 468 publications
(440 citation statements)
references
References 44 publications
40
386
4
9
Order By: Relevance
“…Our finding suggests a plausible mechanism whereby C. trachomatis infection could be associated with increased risk for cervical cancer, as has been reported in several epidemiological studies. 7,[10][11][12]23,24 It has been reported that C. trachomatis infection may induce large local amounts of pro-inflammatory chemokines, including IL-1, IL-8 and granulocyte-macrophage colony-stimulating factor 25 producing a chronic inflammatory background that may conceivably contribute to HPV DNA persistence in the cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding suggests a plausible mechanism whereby C. trachomatis infection could be associated with increased risk for cervical cancer, as has been reported in several epidemiological studies. 7,[10][11][12]23,24 It has been reported that C. trachomatis infection may induce large local amounts of pro-inflammatory chemokines, including IL-1, IL-8 and granulocyte-macrophage colony-stimulating factor 25 producing a chronic inflammatory background that may conceivably contribute to HPV DNA persistence in the cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after infection is initiated, neutrophils are the most predominant effector cells recruited to the infectious foci (Patton and Kuo, 1989;Kiviat et al, 1990), suggesting that PMNs are involved in controlling the early stages of C. trachomatis infection, and confirmed by a study from Barteneva et al (1996). The acute host response to Chlamydia in the genital tract is primarily initiated and sustained by epithelial cells, the first and main targets of chlamydial infection (Rasmussen et al, 1997;Wyrick et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 is one of the most potent C-X-C chemokines and is produced in response to bacterial infection including Chlamydia (Beatty and Sansonetti, 1997;Burns et al, 1997;Rasmussen et al, 1997). Although IL-8 could be detected in culture supernatants of L2-infected HeLa cells as soon as 24 h after infection, the PMN response was detectable only at 36 h after infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations